FOUNDATIONS OF 19TH-CENTURY FRENCH CHILDREN'S LITERATURE - Abdullaeva Nilufar Nasilloevna; Gaybullaeva Gulmira (Bright Mind Publishing, 2025)
This article analyzes the formation and development features of French children's literature of the 19th century. The article covers the following main areas: The socio-historical foundations of French children's literature are considered, including the influence of the ideas of the Enlightenment, the process of industrialization and the development of mass education. The genre features of French children's literature are revealed: the transition from didactic stories to fantastic and adventure works, the typology of new heroes, and the literary traditions that formed during this period are studied.
Keywords: 19th century French literature, children's literature, didactic literature, fantasy literature, Charles Perrault, Jules Verne, Hector Malo, fairy tales, adventure literature, Enlightenment ideas, national identity, education, moral values, social criticism, children's worldview, evolution of literary genres, folklore traditions.